Learners’ Motivation: Stimulus or Stress? - Zaidah Mohd Hashim; Ahmad Muhyiddin; Imran Danial Krish Abdullah; Nurul Hanisah Baharuddin; Mohd Muzhafar Idrus; Noor Hanim Rahmat (Human Resource Management Academic Research Society, 2024)
International Journal of Academic Research in Business and Social Sciences Vol. 1 3 , No. 9 (page: 1384–1404)